Analisis Proses Bisnis Sistem Administrasi Perjalanan Dinas Pada Badan Keuangan dan Aset Daerah Kabupaten Sumedang - Aghitsni, Rofiyandi; Supriadi, Fidi; Junaedi, Dani Indra (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Official travel is a routine activity carried out by state officials, both central and regional. The administrative process carried out during official travel begins with a letter of application for official travel. The application letter that has been approved by the Head of the Regional Work Unit will receive a disposition sheet addressed to the employee. The problem that occurs is that there is an uneven distribution of official travel, where only certain employees are always assigned. Apart from that, official travel costs that are paid in advance before departure trigger the problem of indifferent attitudes in the process of preparing accountability reports. Therefore, a new business process is needed so that this problem does not occur again.